ISLAMIC MODERATION TO REDUCE RELIGIOUS RADICALISM IN INDONESIA - Azad Ali Ismael; Sulastri (Jurnal Multidisipliner Bharasa, 2022)
The issue of radicalism in the name of religion in Indonesia is very worrying. It happened after the reformation that took place in 1998 until Indonesia became the world's spotlight. This research aims to master the extent to which Islamic moderation can reduce religious radicalism in Indonesia. Research procedures use library research. Sources of information come from various readings, especially those related to religious descriptions that can give birth to terrorism. The literature studied, among others, links to sacred texts that serve as justifications in radical movements, which have implications for revolutionary movement actors. The research results show that to reduce radicalism in Indonesia, Islamic Moderation as a middle path is needed, which is compatible with the core teachings of Islam and human nature. Moderate Islam prioritizes the reasonable principle (washatiah) in preaching, which takes the middle path between 2 opposite extreme poles. This Islamic moderation is a method of da'wah that emphasizes the values of Islam rahmatan Lil Alamin. Da'wah is friendly to tradition so that it can grow in a multicultural and multi-religious society.